Analisis Komparatif: Penerapan Hukuman Mati dalam Kasus Pembunuhan di Berbagai Negara - Gunawan Widjaja (Bulletin of Community Engagement, 2024)
This research aims to conduct a comparative analysis of the application of the death penalty in murder cases in various countries. There are significant differences in the policies and practices of the death penalty, with some countries such as the United States and Japan still retaining it, while European countries such as the United Kingdom and Germany have abolished this punishment. Cultural, political, and legal factors influence how the death penalty is applied, for example, in Middle Eastern countries guided by sharia law and in China which has broader and less transparent execution policies. Overall, global trends show a trend toward reducing and abolishing the death penalty, reflecting shifts in social norms and human rights advocacy. This research highlights the importance of considering local context in death penalty policy and supports the need for international dialogue to encourage a more humane and effective implementation of justice